Analysis of the Link between the Redox State and Enzymatic Activity of the HtrA (DegP) Protein from Escherichia coli - Koper, Tomasz (Public Library of Science, 2015)

(untitled) (PLoS One)
Bacterial HtrAs are proteases engaged in extracytoplasmic activities during stressful conditions and pathogenesis. A model prokaryotic HtrA (HtrA/DegP from Escherichia coli) requires activation to cleave its substrates efficiently. In the inactive state of the enzyme, one of the regulatory loops, termed LA, forms inhibitory contacts in the area of the active center. Reduction of the disulfide bond located in the middle of LA stimulates HtrA activity in vivo suggesting that this S-S bond may play a regulatory role, although the mechanism of this stimulation is not known. Here, we show that HtrA lacking an S-S bridge cleaved a model peptide substrate more efficiently and exhibited a higher affinity for a protein substrate. An LA loop lacking the disulfide was more exposed to the solvent; hence, at least some of the interactions involving this loop must have been disturbed. The protein without S-S bonds demonstrated lower thermal stability and was more easily converted to a dodecameric active oligomeric form. Thus, the lack of the disulfide within LA affected the stability and the overall structure of the HtrA molecule. In this study, we have also demonstrated that in vitro human thioredoxin 1 is able to reduce HtrA; thus, reduction of HtrA can be performed enzymatically.